1996
DOI: 10.1002/(sici)1097-0088(199609)16:9<1033::aid-joc77>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Convective Rainfall Regions of Puerto Rico

Abstract: Geographical regions of covariability in hourly precipitation over the island of Puerto Rico are exposed using factor analysis. It is argued that the data are consistent with a common factor model when an orthgonal rotation is applied to the factor loading matrix. The results suggest that Puerto Rico can be divided into six regions, with each region having a similar covariance structure of summer season convective rainfall. The six regions can be grouped into a western area and an eastern area based on contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Night to early morning maxima is found in the central United States (Wallace, 1975), where daytime subsidence inhibits convection (Dai et al, 1999), and India (Sen Roy and Balling, 2007). The interaction of orography and convectional processes, leading to pronounced diurnal cycles in rainfall, was also indicated in smaller island landmasses including Puerto Rico and Hawaii (Carter and Elsner, 1996;Sen Roy and Balling, 2004). In the case of coastal areas, most studies indicate a nocturnal to early morning maximum in the occurrence of rainfall (Schwartz and Bosart, 1979;Chang et al, 1995;Dai, 2001) as we found in that study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Night to early morning maxima is found in the central United States (Wallace, 1975), where daytime subsidence inhibits convection (Dai et al, 1999), and India (Sen Roy and Balling, 2007). The interaction of orography and convectional processes, leading to pronounced diurnal cycles in rainfall, was also indicated in smaller island landmasses including Puerto Rico and Hawaii (Carter and Elsner, 1996;Sen Roy and Balling, 2004). In the case of coastal areas, most studies indicate a nocturnal to early morning maximum in the occurrence of rainfall (Schwartz and Bosart, 1979;Chang et al, 1995;Dai, 2001) as we found in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have emphasized the presence of strong diurnal cycles related with localized convective processes in low latitude tropical areas (Houze et al 1981;Albright et al 1985;Machado et al 1993). Furthermore, the interaction between topography and convection leads to more pronounced diurnal cycles in precipitation (Carter and Elsner, 1996;Sen Roy and Balling, 2004). Ramesh Kumar et al (2006) examined the diurnal cycle of precipitation over the eastern equatorial Indian Ocean from October 2001 to 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Most long-term studies of Puerto Rico's climate have used a limited number of stations, because relatively few stations have a long-term record [30,31], while shorter-term studies make use of the fact that more stations have data available for specific shorter periods, especially since 1960 [15,[21][22][23][24][25][26][27][28][29]32,35,37]. Long-term studies suggest that precipitation has been decreasing in the Caribbean since the 1970s and that droughts in Puerto Rico are periodic [31].…”
Section: Previous Precipitation Studies In Puerto Ricomentioning
confidence: 99%
“…Ewel and Whitmore [20] used long-term station data, vegetation characteristics and forest types to define climate provinces for Puerto Rico. Carter and Elsner [22] used factor analysis with Partially Adaptive Classification Trees to regionalize precipitation. Malmgren and Winter [24] combined artificial neural networks with Principal Components Analysis (PCA) to map precipitation regions in Puerto Rico.…”
Section: Rainfall Mapping and Regionalization Studiesmentioning
confidence: 99%
See 1 more Smart Citation